Tindak Pidana Kawin Ganda Yang Dilakukan Oleh Militer - Nur Janna Samal; Jhon Dirk Pasalbessy; Reimon Supusepa (PAMALI: Pattimura Magister Law Review, 2023)
Introduction: In Indonesia, it is no longer permitted to marry more than one person, unless the marriage has permission in the form of a local District Court decision.Purposes of the Research:  This research aims To review and analyze the basis for the consideration of Military Judges in sentencing TNI members who perform multiple marriages without the permission of legal wives And to review and analyze the application of the Military Criminal Law to TNI members who double marry without the permission of their wives.Methods of the Research: The type of is anormative juridical research, namely a research in the field of law that aims to examine legal principles, legal principles and legal systematics. The legal materials used are primary legal materials, namely binding legal materials and secondary legal materials, namely legal materials that provide an explanation of primary legal materials. The problem approach used in this study is the statutory approach and the conceptual approach.Results of the Research: The results of this study, The application of the Military Criminal Law to TNI members who marry multiple marriages without the permission of a valid wife meets the elements of Article 279 Paragraph (1) to 1 of the Criminal Code declaring marriage or marriages to be a legal obstacle, That based on the consideration of the above considerations, the Panel of Judges stated that the above defendants namely Jufri Lapandewa, Praka NRP 31100265920490,  legally and conclusively proven guilty of a criminal offence: "Double marriage". Convict the Defendant therefore with imprisonment: For 6 (six) months.